Intestinal microbiota variation in Senegalese sole (Solea senegalensis) under different feeding regimes - Marín-Antonio, Beatriz; Manchado, Manuel; Infante, Carlos; Zerolo, Ricardo; Labella Vera, Alejandro Manuel; Alonso, Carmen; Borrego-García, Juan José (Blackwell Publishing Ltd, 2007)
The aim of this studywas to determine the in£uence of the feeding regimes in Senegalese sole (Solea senegalensis) culturedunder extensive, semi-extensive and intensive production systems.Atotal of 254 bacterial isolates from guts of ¢sh cultured under di¡erent production systems and feeding regimes were tested. Biochemical tests and genetic analyses based on the 16S rDNA sequence analysis were conduced to identify bacterial strains.Vibrio species were the most represented taxonomic group in the culturable microbiota of S. senegalensis guts tested. Particularly,Vibrio ichthyoenteri was the most frequently isolatedVibrio species. Comparison among diets showed a signi¢cant reduction (Po0.05) in vibrio percentages and a higher occurrence of Shewanella species in Senegalese soles fed polychaeta. In addition, a major in£uence of environmental temperature on microbiota composition was detected. Cold temperatures brought about a change in the percentages ofVibrio species and a higher representation of a- Proteobacteria in both outdoor systems (extensive and semi-extensive).The signi¢cant di¡erences between intestinal bacterial composition in Senegalese soles fed commercial diets and natural preys (polychaeta) reveal the necessity to develop speci¢c optimized diets for the intensive rearing of this ¢sh species.
Keywords: Lenguados - Alimentación; Solea senegalensis; Intestinal microbiota; 16S rDNA; Feeding regimes; Culture production systems